The relationship between ownership structure and corporate performance in Chinese listed companies - Zheng, Shuhan (2016)
Nowadays, the listed companies have become an essential part of Chinese national economy and the backbone of the social development. The operating performance of those listed companies has attracted the increasing attention those days. The connection and relationship between the ownership structure and the corporate performance have become an important and ongoing issues. This research is not only beneficial in maximizing the own value of the corporate, but also hold significant meaning to the whole national economy. So this research aims to investigate and examine the relationship between the ownership structure and corporate performance by analysing the data in the Chinese listed companies.